Effect of Micropore Filling on Chemisorption by Large Surface Area Materials. Adsorption of O and NO by CuZnO Catalysts - Chaim Aharoni; Bice Fubini; Elio Giamello (Adsorption Science & Technology)
In irreversible chemisorption by large surface area catalysts, the partially covered surface takes up additional amounts of adsorbate only if a given threshold pressure is attained. A model is suggested in which micropore filling acts as a precursor state for other gas-solid interactions. The model is applied to the adsorption of oxygen by CuZnO catalysts with various copper contents, and containing particles and interparticle voids of various sizes.